A Study on Serum Nitric Oxide and Hydrogen Sulfide in Essential Hypertension Cases in a Tertiary Care Hospital in West Bengal - Das, Maumita Naskar; Chaudhuri, Sayani; Ray, Avas Chandra; Kumar, Arun; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2021)
Background-Essential hypertension is a multifactorial disease of unknown etiology characterized by a chronic elevation of blood pressure without any secondary causes. Nitric oxide and hydrogen sulfide are vasodilatory gasotransmitters whose deficiency results in endothelial dysfunction and vasoconstriction and hence is one of the etiological factors in the development of hypertension. Aims and Objectives – The study aimed to estimate the serum levels of NO and H₂S and to find out their correlation in essential hypertension cases and normotensive controls. Materials and Methods- Serum levels of NO and H₂S were measured using chemical methods, in fifty patients with essential hypertension and compared with fifty age-matched controls. Results- The mean serum NOx level in essential hypertension cases is 45.45 ± 11.09 µmol/L which is significantly lower (p-value <0.001) than that of controls where it is 166.40 ± 16.63 µmol / L. The mean serum H₂S level in essential hypertension cases is 45.61 ± 11.01 µmol/ L which is again significantly lower ( p-value <0.001) than controls in which it is 111.54 ± 9.60 µmol/ L. A statistically significant positive correlation exists between serum NOx and H₂S levels in overall study subjects. Conclusion- This study demonstrates that both the serum levels of NO and H₂S decrease with an increase in BP in essential hypertension cases. There exists a positive correlation between NO and H₂S in overall study subjects. Thus, the simultaneous decline in bioavailability of both NO and H₂S is a significant underlying cause in the development of essential hypertension.